How to maintain equity and objectivity in assessing the communication skills in a large group of student nurses during a long examination session, using the Objective Structured Clinical Examination (OSCE). (March 2016) - Bagnasco, Annamaria; Tolotti, Angela; Pagnucci, Nicola; Torre, Giancarlo; Timmins, Fiona; Aleo, Giuseppe; Sasso, Loredana
Summary: Background: While development, testing, and innovation of the Objective Structured Clinical Examination (OSCE) are common in the international literature, studies from the United States of America (USA), Australia, and the United Kingdom (UK) predominate. There is little known about OSCE use in European countries, such as Italy, where other than cost analysis, there is little reporting of OSCE use or validation. Objectives: This paper reports on one Italian initiative, which evaluated the equity and objectivity of the OSCE method of assessing communication skills. Design: An OSCE method was used to assess the communication skills of first-year students of the Degree Course in Nursing. A method of simulation was implemented through role-playing with standardized patients. An observational method was used to collect data. Participants and settings: Four hundred and twenty-one first-year undergraduate nursing students at one university site in Italy took part. Methods: Ten examination sessions were carried out. The students' performances were assessed by two examiners who used a structured observation grid and conducted their assessment separately. A situation simulated by four nurses with experience as actors was used as the topic for the students' examination. Results: Calculation of the daily rate of students who passed the examination revealed a random distribution over time. The nonparametric correlation indexes referring to the assessments and to the scores assigned by the two examiners proved statistically significant ( P  ≤ 0.001). Conclusions: The study confirmed the validity of the OSCE method in ensuring equity and objectivity of communication skills assessment in a large population of nursing students for the purpose of certification throughout the duration of the examination. This has important implications for nurse education and practice as the extent to which OSCE approaches, while deemed objective, are culturally sensitive or valid and reliable across cultures is not clear. This is something that requires further research and examination in this field. Highlights: While OSCE development, testing, and innovation are common in the literature, studies from the USA, Australia, and the UK predominate. Little is known about OSCE use in European countries such as Italy, where other than Palese et al.'s (2012) analysis of its cost, there is little reporting about OSCE. This has important implications for nurse education and practice as the extent to which OSCE approaches are culturally sensitive or reliable across cultures is not clear. This paper is the first reporting an Italian OSCE initiative, which evaluated the equity and objectivity of the OSCE method of assessing clinical learning in one university.